Arsenic, fluoride and other trace elements in the Argentina Pampean plain - Barranquero, Rosario Soledad (2017)
The contents of arsenic, fluoride and other trace elements (As, Cd, Cr, Cu, Fe, Mn, Ni, Pb, V, Zn, Ba, Si and Sr) have been determined in groundwater samples from the Langueyú creek basin, which is located in the Argentinian Pampean plain. This research proposes establishing the baseline concentration and geographical distribution of trace elements in this basin. This aim has particular interest to public health in the city of Tandil where groundwater is the principal source of water for human supply. The baseline concentrations of elements in the Langueyú creek basin were in good agreement with published data from other locations of the Pampean aquifer. The arsenic limit of 10g/l, established as provisional limit by the World Health Organization (WHO), was exceeded in 78% of sampled wells, with As concentration increasing in the direction of groundwater flow. Concentrations of other trace elements (B, Cd, Cu, Cr, Fe, Mn, Ni, Pb and Zn) regulated by the Argentinian Food Code (CAA) do not exceed the maximum limit for drinking water, although concentrations of Ni, Zn or Pb peaked up at some wells, probably due to pipeline corrosion. The strong correlation observed between As, F, V, Cr and B has been related to their anionic character at the groundwater natural alkaline pH that is likely associated to similar mobilization (adsorption/desorption) processes. Although the worst consequences for human health have arisen in areas with the highest arsenic concentration in drinking water, this study is relevant in relation to the public health as it contributes to understand the provenance and mobilization processes of some trace elements in groundwater, thus enabling the decision making regarding the priorities of technological treatments in urban and rural areas.